Woolf and the City. - Evans, Elizabeth F. (Woolf Selected Papers LUP., 2010)
Woolf and the City collects important essays selected from the nearly 200 papers delivered at the nineteenth annual international conference on Virginia Woolf. The volume includes an introduction by the editors, the conference keynote addresses, and twenty-five essays organized around six presiding themes: Navigating London; Spatial Perceptions and the Cityscape; Regarding Others; The Literary Public Sphere; Border Crossings, and Liminal Landscapes; and Teaching Woolf, Woolf Teaching. It also includes a special session of the conference, a round-table conversation on Woolf's legacy in and out of the academy. Beyond the volume's focus on urban issues, many of the essays address the ethical and political implications of Woolf's work, a move that suggests new insights into Woolf as a "real world" social critic. The contributors, who include Ruth Gruber, Molly Hite, Mark Hussey, Tamar Katz, Eleanor McNees, Kathryn Simpson, and Rishona Zimring, advance Woolf studies and the broader fields of narrative studies, cultural geography, urban theory, phenomenology, and gender studies.